Carbon-Intensive Path Dependencies in the Electric Grid: Assessing the Effect of Coal-Fired Power Plant Closures on Future Renewable Energy Adoption - Steinberg,Cole Anderson (2020)
Increasingly severe consequences of fossil fuel consumption have proliferated the exigency of an energy transition to zero and low-carbon electricity generation technology. Despite its relative reduction in market share in the United States, coal continues to play a role in future energy scenarios. This study examines the contiguous U.S. by combining historical data on coal-fired power plants with modeled energy scenarios. It contemplates the theoretical concept of carbon lock-in and what effects historical reduction of coal capacity has on future renewable energy adoption. The study employs econometrics utilizing multivariate regression analysis to approach a set of hypotheses related to technical, economic, and political considerations of the energy transition. The main findings are that (1) historical reduction in available coal capacity from 2004-2019 is positively correlated with higher renewable energy capacity in 2050 in absolute volumes, yet (2) the greater capacity does not translate into an increased share of renewables as a fraction of the total energy portfolio in 2050. Therefore, coal closures may increase the capacity of renewables but renewable capacity growth does not axiomatically entail a contraction of fossil fuels. This distinction suggests that further research should be directed at policy approaches that not only generate higher renewable growth, but reduce the total quantity of fossil fuels to advance renewables as the dominant technological design.
Keywords: Energy Transition; Coal Closures; Renewable Energy; Carbon Lock-In; Fuel-Switching